Pengaruh Kombinasi Media Tanam Terhadap Perkecambahan Benih Merbau (Intsia bijuga (Colebr) O. Kuntze) - Mariana Fridolin Bete Louk; Astin E. Mau; Norman P. L. B. Riwu Kaho; Pamona S. Sinaga (Wana Lestari, 2026)
Merbau (Intsia bijuga (Colebr.) O. Kuntze) is a plant species widely utilized due to its high economic value and is well-known for export purposes. This study aims to determine the effect of planting media combinations on the germination of merbau seeds. The study used a completely randomized design (CRD) with a single factor, consisting of five treatments: M0 (control), M1 (850 grams of soil + 150 grams of rice husk biochar), M2 (850 grams of soil + 150 grams of chicken manure), M3 (850 grams of soil + 50 grams of rice husk biochar + 100 grams of chicken manure), and M4 (850 grams of soil + 100 grams of rice husk biochar + 50 grams of chicken manure), each with three replications. Further testing was conducted using Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that the combination of planting media significantly affected the parameters of Germination Power, Germination Speed Index, and Germination Value. These three parameters showed the highest significant differences, respectively: 96.667%, 1.168, and 0.206, in the M3 treatment or the combination of planting media (850 grams of soil + 50 grams of rice husk biochar + 100 grams of chicken manure).